2012
DOI: 10.1002/jbm.a.34018
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐small‐angle X‐ray scattering–X‐ray photon correlation spectroscopy studies of incipient structural changes in amorphous calcium phosphate‐based dental composites

Abstract: The local structural changes in amorphous calcium phosphate (ACP) based dental composites were studied under isothermal conditions using both static, bulk measurement techniques and a recently developed methodology based on combined ultra-small angle X-ray scattering – X-ray photon correlation spectroscopy (USAXS-XPCS), which permits a dynamic approach. While results from conventional bulk measurements do not show clear signs of structural change, USAXS-XPCS results reveal unambiguous evidence for local struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…We attribute the first, smaller population to the primary particles and the second, larger population to the aggregation of the primary particles. These results are consistent with the findings of a wide range of in vivo and in vitro ACP studies [12, 16, 17, 47, 48]. Additionally, with assistance from the contrast parameters in Table 2 , we found that the total scattering volume fraction of the ACP was about 0.26 ± 0.04, which yields a mass fraction of ACP at 0.37 ± 0.04.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…We attribute the first, smaller population to the primary particles and the second, larger population to the aggregation of the primary particles. These results are consistent with the findings of a wide range of in vivo and in vitro ACP studies [12, 16, 17, 47, 48]. Additionally, with assistance from the contrast parameters in Table 2 , we found that the total scattering volume fraction of the ACP was about 0.26 ± 0.04, which yields a mass fraction of ACP at 0.37 ± 0.04.…”
Section: Resultssupporting
confidence: 91%
“…We have previously established that for this type of ACP filled dental composite bulk characterization methods are not adequately sensitive to detect the local and subtle structural changes in the amorphous fillers [48]. XPCS, on the other hand, is an interferometric technique based on monochromatic coherent X-rays.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…33,34 The composite polymer nanofibers were produced using a two-step process: (a) mixing Zr-ACP powder with solvent and polymer and (b) airbrushing the composite onto TCPS discs.…”
Section: Polymer Composite Nanofiber Fabricationmentioning
confidence: 99%